In vitro performance of combinations of anti-siphon devices with differential pressure valves in relation to the spatial position - Fiss, I.; Vanderheyden, M.; von der Brelie, C.; Bettag, C.; Hore, N.; Freimann, F.; Thomale, U. W.; Rohde, V.; Brandner, Sebastian (Acta Neurochirurgica, 2020)
Background: Programmable differential pressure (DP) valves combined with an anti-siphon device (ASD) represent the current standard of care in preemtping overdrainage associated with ventriculoperitoneal shunting for hydrocephalus. Objective: We aimed to provide comparative data of four combinations of two ASDs of different working principles in combination with two DP valves in an in vitro model in order to achieve a better understanding of the flow characteristics and potential clinical application. Methods: We analyzed the flow performance of four possible combinations of two DP valves (CHPV [HM]; proGAV 2.0[PG]) in combination with either a gravity-regulated (Shuntassistant [SA]) or a flow-regulated (SiphonGuard [SG]) ASD in an in vitro setup. A DP between 4 and 60 cmH2O was generated, and the specific flow characteristics were measured. In addition, the two combinations with gravity-regulated ASDs were measured in defined spatial positions. Results: Flow characteristics of the SA combinations corresponded to the DP in linear fashion and to the spatial position. Flow characteristics of the SG combinations were dependent upon the DP in a non-linear fashion and independent of the spatial position. Highest mean flow rate of the PG-SG- (HM-SG-) combination was 1.41 ± 0.24 ml/min (1.16 ± 0.06 ml/min). The mean flow rates sharply decreased with increasing inflow pressure and subsequently increased slowly up to 0.82 ± 0.26 ml/min (0.77 ± 0.08 ml/min). Conclusion: All tested device combinations were able to control hydrostatic effect and prevent consecutive excessive flow, to varying degrees. However, significant differences in flow characteristics can be seen, which might be relevant for their clinical application.
CRIS-Team Scopus Importer:2020-02-07
Keywords: Anti-siphon device; Hydrocephalus; Overdrainage; Shunt valve